Pengaruh Strategi Pemasaran Dan Perilaku Konsumen Terhadap Volume Penjualan Treadmill Pada CV. GAF Tridaya Mandiri - Ama Suyanto; Muhammad Dwi Sa`di (Journal of Economic, Bussines and Accounting (COSTING), 2023)
This research was made with the aim of knowing the marketing strategy for treadmill products, knowing the effect of marketing strategy on sales volume and knowing the effect of consumer behavior on sales volume at CV. GAF Tridaya Mandiri. This type of research is field research using a quantitative descriptive approach. The population in this study are all consumers of CV. GAF Tridaya Mandiri, because there are many of them and it is not known with certainty, the authors are looking for samples using the Bernoulli Formula so that the number of samples in this study is 400 respondents. The sampling technique used is non-probability sampling. The analysis used is multiple regression analysis. The results showed that the variables marketing strategy, consumer behavior and sales volume have an average weight in the very good category, simultaneously marketing strategy and consumer behavior have a significant effect on sales volume and the magnitude of the influence is 40.3%. Partially both marketing strategy and consumer behavior, each variable has a significant effect on sales volume. Based on the research findings, the research contribution certainly influences the company, both in increasing sales volume and company profits, therefore the authors can provide suggestions for each indicator of each variable that has the smallest weight that needs to be improved again. Keywords: Marketing Strategy, Consumer Behavior, Sales Volume.